The Clinical Impact of Daptomycin Non-susceptible Enterococcus Bacteremia in Hematologic Malignancy. (4th October 2017) - Lee, Rachael A; Kaye, Keith S; Cutter, Gary; Camins, Bernard
Abstract: Background: Patients with hematologic malignancies are prone to colonization and infection with vancomycin-resistant E nterococcus (VRE), and VRE blood stream infections (BSI) in this population have been associated with a 30-day all-cause mortality approaching 40%. Daptomycin nonsusceptible Enterococci (DNSE) are on the rise, with institutional rates as high as 15%. The objective of this study was to determine the attributable mortality associated with resistance to daptomycin among VRE isolates. Methods: We performed a retrospective cohort study of hematologic malignancy patients who developed either DNSE or daptomycin-susceptible VRE bacteremia between January 1, 2008 and December 31, 2016. Categorical variables were analyzed with chi-square or Fisher's exact test and continuous variables were analyzed with a t-test or Wilcoxon rank sums test when appropriate. A p-value <0.05 was considered significant. Results: 34 cases of DNSE and 65 cases of VRE were identified. There were no significant differences noted in demographic data. At time of bacteremia, both DNSE and VRE cohorts had similar APACHE II scores (medians for DNSE and VRE were 19). The DNSE cohort had longer periods of neutropenia prior to the diagnosis of bacteremia [median 32.1 days vs.. 19.3 days, OR 1.85 95% CI (0.75-1.60)]. Patients with DNSE had a longer time to initiation of appropriate antibiotics (median 3.5 days vs. 2.0 days, P = 0.01). There were similar rates of bone marrow transplantation (53 % of DNSE vs. 51% of VRE), however, DNSE cases were more likely to develop graft vs. host disease [OR 3.6 95% CI (1.07-12.38)]. In the 90-day period prior to bacteremia, daptomycin exposure occurred in only 12 (35.3%) of DNSE cases vs.. 1 (1.5%) VRE case [OR 34.9 95% CI (4.3-284.1)]. Median lengths of stay (LOS) were similarly high in both groups, however, DNSE patients were more likely to have a LOS over 50 days as compared with VRE (P = 0.048). 30-day mortality in the DNSE cohort was 50% compared with 38% in the VRE group (P = 0.12). Conclusion: In a retrospective study, the 30-day mortality associated with DNSE bacteremia was 50%. Infection prevention interventions targeting this particular multi-drug-resistant organism are warranted in this vulnerable population. Disclosures: All authors: No reported disclosures.